DFT studies of surface‐enhanced Raman spectroscopy of 1, 4‐benzenedithiol–Au2 complex under the effect of static electric fields. (12th October 2015) - Zhang, Yanxiao; Shao, Yangfan; Zhang, Wanwan; Feng, Yuanming; Lin, Wang
Abstract : In this work, we demonstrate that the applied electric‐field strength and orientation can multiply modulate the Raman intensity and vibrational wavenumber of small molecule–metal complex, 1, 4‐benzenedithiol–Au2 (1, 4BDT–Au2 ), by density functional theory and time‐dependent density functional theory simulations. The polarizabilities are changed by the applied electric fields, leading to enhanced specific vibrational intensity and shifted vibrational wavenumber of the surface‐enhanced Raman scattering effect. The applied electric fields perturb the bonds and angles of the 1, 4BDT–Au2 complex. Owing to this reason, the peaks of Raman spectra related to these structures exhibit distinguishable responses in quasi‐static field (low‐frequency oscillating electric field). We use the visualized method of charge difference density to show that the electric fields tune the traditional excited state to pure charge‐transfer excited state. The charge‐transfer resonance transition produces enhanced Raman intensities for non‐totally symmetric modes and totally symmetric modes. These simulation results of the function of static electric field provide new guidance for the surface‐enhanced Raman scattering measurements. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The DFT studies demonstrate that the applied electric‐field strength and orientation can multiply modulate the Raman intensity and vibrational frequency of the molecule–metal complex, 1, 4‐benzenedithiol–Au2 . The charge transfer from metal to molecule selectively enhances the Raman intensities of non‐totally symmetric modes and totally symmetric modes. These simulation results provide new guidance for tuning and controlling the SERS measurements in static electric field.